Biogenically modified reservoir rock quality: A case from the lowermost member Paleocene Funing Formation, Gaoyou Depression, Subei Basin, China - Quaye, Jonathan Atuquaye; Jiang, Zaixing; Liu, Chao; Adenutsi, Casper Daniel; Boateng, Cyril D. (Journal of Petroleum Science and Engineering, 2024)
This article is published in Journal of Petroleum Science and Engineering 219 (2022) 111126; https://doi.org/10.1016/j.petrol.2022.111126